The Plural of Anecdote Is “Blog” - A. Michael Froomkin (Washington University Law Review, 2006)
Evaluating the limitations and benefits of blogging as a form of legal scholarship, this paper ultimately asks the question -- what are blogs good for? This paper puts forth the argument that law blogs are a great tool for the sharing, organization, and development of ideas. At the same time, the limitations of blogging when dealing with complex, lengthy material are recognized.
Keywords: Law -- Study & teaching; Blogs; Legal literature; United States